Prognostic factors and survival of endometrial cancer: An 11-year retrospective cohort study in southern Taiwan - Ruo-Shi Bing; Dah-Ching Ding; Chun-Shou Hsu (Elsevier, 2024)
Objective: Endometrial cancer (EC) is the most common gynecological malignancy in high-income countries. In Taiwan, the incidence of EC increased from 1.69 in 1980 to 11.36 per 100,000 women/year in 2010. Therefore, we aimed to study the prognostic factors and survival of patients with EC in southern Taiwan. Materials and methods: This study included patients with EC who underwent hysterectomy-based surgery at our hospital between 2010 and 2020. The primary outcome was 5-year progression-free survival (PFS) and overall survival (OS) of patients diagnosed with EC. The secondary outcome was the prognostic factors associated with 5-year PFS and OS in patients with EC. We used the chi-square test to assess categorical variables and the independent t-test to assess continuous variables. The Kaplan-Meier method was used to estimate survival outcomes. Cox regression analysis was conducted to examine the factors associated with PFS and OS. Results: A total of 133 patients were enrolled in this study. The mean age of the patients was 56.5 ± 10.71 years. The mean body mass index was 26.4 ± 5.21 kg/m2. The 5-year PFS and OS were 90.3% and 94.53%, respectively. In terms of PFS, endometrioid histology was linked to more favorable outcomes (hazard ratio [HR] = 0.02, 95% confidence interval [CI]:0.001-0.59), while lymph-vascular space invasion (LVSI) was associated with adverse results (HR = 9.11, 95% CI: 1.07-77.44). Initial analyses revealed no significant correlations between OS and various factors, including age, BMI, parity, DM, hypertension, age at last birth, and tumor grade. However, univariate analysis found grade 3 tumor differentiation, LVSI, and lymph node invasion associated with poorer OS. Laparoscopy was associated with better OS. Nevertheless, subsequent multivariate analysis did not reveal any factor significantly associated with OS. Most patients with EC (76.69%) underwent laparoscopic surgery. Conclusion: In conclusion, endometrioid histology was linked to more favorable PFS, while LVSI was related to adverse PFS. Our study did not identify any factors associated with OS. Two-thirds of the patients underwent minimally invasive surgery.